Improving management in communities through qualification in project formulation (Revista cientifica In Vestigium Ire, 2021)
It is the most popular neighborhoods that are left behind in urban development and with deficiencies in the infrastructure of support services, and although there is internal administrative progress from thecommunity action boards (JAC); But since they do not have the knowledge and tools to help them in that management, they will continue to have difficulties in processing the solutions that give optimal urban development to their neighborhoods.The objective of this article is to support and strengthen the community action board of the Barrio Cooservicios of the municipality of Tunja, through the social appropriation of knowledge, providing training in the formulation of social infrastructure projects through the application of the MGA logical framework methodology, that constitutes an important point in the development of their territories and strengthens their social alliance.A community that has knowledge in project formulation through the Adjusted General Methodology will have a tool that will allow them to access in a more agile way the possibility of attracting state resources to solve the various problems of their locality.
Keywords: Community management; Project formulation; Methodologies